Natural products as anticancer agents and enhancing their efficacy by a mechanism-based precision approach - Stephen Safe (Exploration of Drug Science)
Traditional medicines and their active ingredients and some natural products and derived analogs have been used for treating multiple diseases including cancer. Among these compounds cytotoxic agents such as bleomycin, paclitaxel and vincristine block essential pathways and genes required for cancer cell growth and these agents have diverse clinical applications. Dietary phenolics including flavonoids and related compounds are associated with multiple health benefits however most individual dietary compounds and other natural products that show promising anticancer activity in preclinical studies exhibit minimal clinical effectiveness and this is particularly true for cancer. Many of the compounds perform poorly in clinical trials due to pharmacokinetic consideration and limited uptake (e.g., curcumin) and these are issues that can be addressed. The clinical effectiveness of flavonoids and many other natural product-derived anticancer compounds can also be enhanced by a more targeted approach. This would include identifying a significant response/gene or target in a specific cancer and then identifying the optimal compound. In this review, I have discussed a limited number of targets including non-oncogene addiction genes such as Sp transcription factors, reactive oxygen species (ROS) or the orphan nuclear receptor 4A (NR4A) sub-family. Thus, the most active compound for these responses could be used only for treating patients that are ROS-inducible or highly express targets such as Sp1 or NR4A sub-family members. A mechanism-based precision medicine approach should enhance the clinical efficacy of dietary and related natural products as anticancer agents and decrease toxic side effects for some combination therapies.